Antibacterial Activity of N-Hexan and Ethyl Acetate Fractions of Gaharu (Aquilaria Malaccensis) Leaves against Bacteria that Cause Infection - Yahya, Fifi Adelia; Herwin, Herwin; Fitriana, Fitriana (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Gaharu (Aquilaria malaccensis) leaves contain alkaloids, terpenoids, flavonoids, saponins, and tannins that can help cure infections. This study aims to determine the antibacterial activity of n-hexane and ethyl acetate fractions of Gaharu leaves against skin infection bacteria such as Propionibacterium acnes, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis by Bioautography-TLC. Gaharu leaves symplisia was extracted using the maceration method using ethanol 96% solvent and fractionation with solid-liquid method to obtain n-hexane and ethyl acetate fractions. The result of the screening antibacterial activity of n-hexane and ethyl acetate fractions of Gaharu leaves with concentrations of 0,5% active to 4 bacteria test. The results of antibacterial activity n-hexane and acetaet ethyl fraction by Bioautography-TLC using n-hexane:ethyl acetate (1:4) eluent showed Rf 0.67 and Rf 0,16 value in the n-hexane fraction and an Rf 0.78 value in the ethyl acetate fraction active to 4 bacteria test. The identification results of the chemical compound of the n-hexane fraction contain flavonoids and tannins (AlCl3 and FeCl3 reagents.), the ethyl acetate fraction contains flavonoids ( AlCl3 reagents).